Analysis of plasticization and reprocessing effects on the segmental cooperativity of polylactide by dielectric thermal spectroscopy. (3rd May 2021) - Pascual-Jose, B.; Badia, J.D.; Múgica, A.; Addiego, Frédéric; Müller, Alejandro J.; Ribes-Greus, A.
Abstract: In the present study, the dielectric properties of both neat and plasticized polylactide submitted to repeated extrusion and injection processes to simulate recycling were analysed. The dielectric relaxation spectrum, consisting of β and α relaxation, revealed the relevance of both acryl-PEG based plasticization and thermo-mechanical degradation induced by repeated extrusion and grinding-injection reprocessing cycles on polylactide (PLA). The β-relaxation has its origin in the intramolecular local motions of pendant groups of the PLA backbone, while the α-relaxation is representative of the intermolecular large-scale segmental motions of the PLA backbone. The addition of acryl-PEG to PLA (pPLA) induced an increment in the apparent activation energies and temperatures of the β-relaxation due to the different nature of the acryl-pendant group in pPLA. Moreover, the crystallization rate of pPLA was much faster compared to that of neat PLA, which hindered the movements of the acryl-pendant group, thus requiring more energy to orient the dipoles. The plasticizing effect of acryl-PEG effectively aids the large-scale motions associated to the glass transition, which are the origin of the α-relaxation. The effect of reprocessing in PLA is less relevant than the addition of the acryl-PEG plasticizer, in terms of dielectric behaviour. With increasing the number of processing cycles, the crystallization rate of PLA gradually increased, but the permittivity was still much lower than that of pPLA, for which crystallinity remained constant. Nonetheless, for the case of the α -relaxation of pPLA, the rearrangements produced by chain scission induced an enhancement of the thermal activation of the orientation of the dipoles but reduced the dynamic fragility and increased the embrittlement of pPLA after reprocessing. These differences found in the relaxation spectrum and the molecular dynamics in the environment of the glass transition for PLA and pPLA, together with the embrittlement of pPLA after reprocessing, is what will determine the final use of one or the other recycled polymer. Graphical abstract: Image 1 Highlights: Reprocessing was less relevant than the addition of the acryl-PEG on the spectra. Acryl-PEG plasticization increased the dielectric permittivity of PLA. The E a of the β -relaxation of pPLA increased as it crystallized much faster. Acryl-PEG plasticization decreased the Tg peak more than reprocessing. Reprocessing diminished more the dynamic fragility of pPLA than PLA.